2015
DOI: 10.1038/tpj.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

AGXT and ERCC2 polymorphisms are associated with clinical outcome in metastatic colorectal cancer patients treated with 5-FU/oxaliplatin

Abstract: The objective of the study was to investigate whether specific single nucleotide polymorphisms (SNPs) with influence on drug transport, biotransformation and repair mechanisms are associated with treatment outcome and toxicity in metastatic colorectal cancer (mCRC). We genotyped blood samples from 519 mCRC patients treated with first-line 5-fluorouracil and oxaliplatin +/- cetuximab for 17 SNPs in 10 genes involved in membrane transport (ABCC1 and ABCC2), drug biotransformation (GSTP1 and AGXT) and DNA repair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
5
11
0
Order By: Relevance
“…In general, neither 5-year RFS or OS were associated with any of the polymorphisms in the present study with the exception of the ERCC2-rs238406 C allele that was associated with significantly shorter 5-year OS among stage I and II CRC patients. Our results are in agreement with one study in Nordic population that showed patients with the ERCC2-rs238406 A/A genotype had a significantly longer progression-free survival compared to patients with the C/A and C/C genotypes [39]. There was no significant difference, however, in the OS.…”
Section: Survivalsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, neither 5-year RFS or OS were associated with any of the polymorphisms in the present study with the exception of the ERCC2-rs238406 C allele that was associated with significantly shorter 5-year OS among stage I and II CRC patients. Our results are in agreement with one study in Nordic population that showed patients with the ERCC2-rs238406 A/A genotype had a significantly longer progression-free survival compared to patients with the C/A and C/C genotypes [39]. There was no significant difference, however, in the OS.…”
Section: Survivalsupporting
confidence: 92%
“…Treatment induced toxicity is an important factor that eventually can result in either dose reduction or termination of the treatment [39]. In our study patients receiving FLV or oxaliplatin-based adjuvant therapy, the ERCC1-rs11615 genotype T/T was significantly associated with stomatitis, while among patients receiving first-line chemotherapy, the ERCC1-rs11615 C allele was associated with nausea.…”
Section: Polymorphisms and Toxicitymentioning
confidence: 68%
See 1 more Smart Citation
“…Haematological toxicity was also reported in a previous study, where the ERCC2-rs13181 C allele was significantly associated with an increased risk of FOLFOXinduced toxicity [44]. These results can partly be explained by the fact that both the ERCC2-rs13181 C allele and the ERCC2-rs238406 C/C genotype are associated with reduced enzyme activity and suboptimal DNA repair, leading to increased sensitivity of normal cells to DNA-damaging agents like oxaliplatin [6,17,42]. No association between XRCC1 polymorphism and any of the investigated toxicity parameters was however found.…”
Section: Polymorphisms and Toxicitysupporting
confidence: 65%
“…Treatment-induced toxicity is an important factor that eventually can result in either dose reduction or termination of the treatment [42]. In our study of patients receiving adjuvant FLV or FLOX therapy, the ERCC1-rs11615 genotype T/T was significantly associated with stomatitis, and among patients receiving first-line chemotherapy, the ERCC1-rs11615 C allele was associated with nausea.…”
Section: Polymorphisms and Toxicitymentioning
confidence: 66%